Thermal comfort assessment of the first residential Passivhaus in Latin America. (November 2021) - Moreno-Rangel, Alejandro; Sharpe, Tim; McGill, Gráinne; Musau, Filbert
Abstract: New approaches to building design, such as the Passivhaus standard, aim to minimise energy consumption and improve indoor environmental comfort. In 2014, the first Passivhaus dwelling in Latin America was built, and since then, other buildings have followed this approach. However, there is little published data on thermal comfort in Passivhaus certified dwellings in non-European countries. No previous study has evaluated the thermal comfort in Passivhaus buildings in Latin America. This work aims to assess the annual overheating of the first Passivhaus dwelling in Mexico City following the Passivhaus, static (CIBSE Guide A, Passivhaus, Mexican standards) and dynamic (Adaptive approach – CIBSE TM52) methodologies to assess overheating. Indoor temperature and relative humidity were measured over one-year at 5-min intervals. Temperatures above 25 °C were observed in the bedroom during 7.53% of the year, the living room (8.03%) and the kitchen (8.20%). There was a significant daily temperature variation in the kitchen (4.15 °C) and living room (6 °C). Overheating was observed through the CIBSE Guide A static criteria in the bedroom and kitchen. The Adaptive and Passivhaus criteria suggested no overheating. Passivhaus overheating criteria sets indoor temperatures as acceptable. Occupant perception of thermal comfort matched the Adaptive and Passivhaus criteria results. While the results presented here cannot be generalised, they could be used to help improve the design and performance of Passivhaus certified dwellings in similar climates'. The results highlight the potential for Passivhaus dwellings to provide comfortable indoor environments while minimising energy consumption in Latin American countries. Highlights: Overheating assessment of the first certified Passivhaus dwelling in Latin America. Static—CIBSE, Passivhaus, Mexican Standards—and dynamic—CIBSE TM52—criteria applied. The TM52 and Passivhaus analysis indicated that the Passivhaus was thermally comfortable. The temperature during April and May were the most critical. Future research is needed to inform the adoption of Passivhaus in Latin America.